Overview of the operational service quality in UAE Government - Kasim, Rozilah; Al Meqbaali, Salem R. (Penerbit UTHM, 2018)
Government service providers now play a growing important role in the general economy of some countries. The purpose of this study is to determine the operational service quality in United Arab Emirates (UAE) government. Fundamentally, there is a need to identify the issues of impact of government operational service quality towards service quality in the UAE. The most popular model used among general instruments for evaluation of service quality is SERVQUAL, which is being the most effective and mostly used model in service quality evaluation. Service quality is a sort of dimensions that reflects several things, such as reliability, responsiveness, assurance, empathy, tangible etc. In order to understand the research phenomenon of the operational service quality in UAE government service, this research basically emphasizes on the precedent literatures. Since this is a conceptual paper, this study establishes the need the operational service quality in UAE government service by empirically and theoretically. In depth findings show that, effective measurement of service quality and excellence for various dimensions of Government service could be very useful in the segmentation of customers and the allocation of resources. Government sectors could focus on different customer needs and the service quality dimensions, which are crucial in achieving operational service quality.